Role of digital education through smartphones in improving knowledge among asthma patients: A preliminary study - Pohan, Indah TS.; Tarigan, Amira P.; Pandia, Pandiaman; Mutiara, Erna (Narra Sains Indonesia, 2024)
Asthma is a chronic inflammatory airway disorder and is among the top ten causes of morbidity and mortality in Indonesia, highlighting the need for effective management strategies. This study aimed to evaluate changes in asthma knowledge levels before and after using the